The social and solidary economy of the BioFeria Miraflores - Chuspe Apaza, Keyko (2017)
This document is the result of a research / action group. The work which seeks to examine the dynamics of production and marketing in the Bioferia de Miraflores, in Lima city. It emphasizes four aspects: a. its history (organizational memory), b. internal relationship (type of organization), c. external relationship (with the environment Bioferia) and d. the projection having the Bioferia medium and long term. During the exam will be able to know and find elements of social and solidarity economies, drawing attention to this kind of development, which seeks located outside the neoliberal market logic and is presented as an alternative to be considered within of capitalist rationality in which we are immersed even in regard to the academy. This test allows to continue discussing the social and solidarity economy as an alternative to production imposed by the free market. As well as to meet different rationales that are based on economic output as the type of organization that this demand, which in this case food sovereignty and ecological marketing based on organic products, you need to rescue.